(3GdGJLGQ aj GdHTQ Hjf GdGbJUGO GdNaj h GdGbJUGO GdQSej (B/s - (3fGTO, ShRj YOdjs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2005)
(3GdecJHI GdbGfhfjI GdeXGgQ GdNQLjI ddGJLGQ HGdHTQ (B: (3eaghe GdGJLGQ aj GdHTQ h GdGSJZdGd GdLfSj , JLGQI GdGTNGU h YeGdI GdGWaGd h JLGQI GdGYVGA , GdGfYcGSGJ GdGbJUGOjI dXGgQI GdGJLGQ aj GdHTQ (B.s
Keywords: (3GdGbJUGO GdNajs; (3GdHZGA`` JLGQIs; (3GdJLGQIs